(untitled) (Global Journal of Medical Research, 2023)
Analysis of the archival material of the Ukrainian Research Institute of Prosthetics made it possible to determine the structure of the primary referral of children with spinal deformities to the clinic over the past 10 years The following factors were assessed age gender type of deformity magnitude of deformity Cobb and bone age Risser These data determine the strategy and tactics of treatment and form the basis of its prognosis At the same time the timeliness of the child s parents contacting a specialist is significantly influenced by a number of factors that depend on the organization of healthcare in the country The generalized material made it possible to create a clinical portrait of a patient who sought help from a specialist for the first time This is a female child aged 11 - 13 years with unfinished bone growth Risser test 2 - 3 right-sided thoracic spinal deformity of the 2nd degree The results obtained do not contradict literature sources and indicate the wide potential of conservative treatment in achieving positive results